Influence of physical and chemical factors during foraging and culture of the symbiont fungus in Atta sexdens rubropilosa (Hymenoptera : Formicidae) - Verza, Sandra S.; Forti, Luiz Carlos [UNESP]; Lopes, Juliane F. S.; Camarg, Roberto S.; de Matos, Carlos A. O. (Wiley-Blackwell, 2007)
The aim of this paper is to investigate the influence of physical and chemical factors on transport and use of substrate for Atta sexdens rubropilosa workers. Three types of rectangular fragments were used to study the physical influence factors: filter paper with paraffin, filter paper without paraffin and polyester film. To study the chemical factors, some fragments were impregnated with organic extract of orange albedo, others were soaked with soybean oil and for the remaining ones nothing was applied. The following parameters were evaluated: (i) attractiveness of substrate for transport and number of loading workers per treatment; (ii) foraged material incorporation; (iii) rejection by numbers of fragments deposited in the garbage or beside the fungus garden. All the polyester film fragments carried out to the fungus garden were subsequently rejected. We verified that chemical factors of the substrate were more quickly detected by the workers, whereas physical factors were used as a criterion in the decision-making to reject or accept the substrate collected.
Keywords: Atta sexdens rubropilosa; attractiveness; behavior; leaf-cutting ants; substrate; rejection; substrate selection